The role of sodium driven bicarbonate transporters in triple negative breast cancer metastasis - Carroll, Christopher (2020)
Triple negative breast cancer is the most difficult breast cancer subtype to treat due to; hormonal therapy resistance, regions of hypoxia, propensity to metastasize, and a lack of targeted therapy options. Metastasis is the cause of over 90% of breast tumour deaths. Hypoxic regions are areas of low oxygen and arise in tumours due to a high metabolic and proliferative rate, and aberrant vasculature. Hypoxia induces resistance to chemotherapy and radiotherapy. Hypoxic tumour regions are also generally more acidic, both hypoxia and acidosis induce metastasis. The sodium driven bicarbonate transporter (NDBT) family regulate intracellular pH. Preliminary data has shown that under hypoxic conditions (0.5% O2) NDBT mRNAs are induced in triple negative breast cancers and knockdown of one of these (SLC4A9) or NDBT inhibition reduces migration and invasion in-vitro. The aim of this PhD was to investigate targeting NDBTs as a novel mechanism for inhibiting triple negative breast cancer metastasis.